Pengaruh Media Sosial Instagram dan Kelas Sosial terhadap Perilaku Konsumtif (Studi Kasus pada Karyawan Produktif PT. Moya Kasri Wira Jatim Pandaan) - Maghfiroh (CV. Satria Jaya, 2023)
This research aims to determine the influence of social media Instagram and social class, either partially or simultaneously, on consumer behavior. The population in this study were production employees of PT. Moya Kasri Wira East Java Pandaan. The sampling technique used random sampling with a total of 104 respondents. The data collection technique is in the form of a questionnaire. The data analysis technique uses multiple regression analysis. The research results show: (1) there is a positive and significant influence of Instagram social media on the consumer behavior of PT production employees. Moya Kasri Wira East Java Pandaan. (2) there is a positive and significant influence of social class on the consumptive behavior of production employees of PT. Moya Kasri Wira Jatim Pandaan. (3) there is a simultaneous influence of Instagram social media and social class on the consumptive behavior of PT. Moya Kasri Wira Jatim Pandaan production employees